Estratégias de legitimação linhagística em Portugal nos séculos XIV e XV - Fernandes, Fátima Regina (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
In this work we seek to analyse the superimposition of the legitimate and first-born branch of the Pereiras, in the second half of the 14th century, by the illegitimate collateral branches, mainly through two individuals. After the disappearance of these protagonists of the Portuguese socio-political scene, one verifies that their projection occurs in later times by means of the historiographical sources.